2003
DOI: 10.1590/s1519-69842003000100017
|View full text |Cite
|
Sign up to set email alerts
|

Helminths infecting Mabuya dorsivittata (Lacertilia, Scincidae) from a high-altitude habitat in Itatiaia National Park, Rio de Janeiro State, Southeastern Brazil

Abstract: We analysed the helminth fauna associated with the lizard Mabuya dorsivittata (Scincidae) from a high-altitude area in Itatiaia National Park, Rio de Janeiro State, Brazil. Of the 16 lizards examined, 12 (75%) were infected by at least one helminth. Only two helminth species were found: Physaloptera retusa and Skrjabinodon spinosulus (Nematoda), the former with a prevalence of 68.8% and a mean infection intensity of 3.6 +/- 2.8 and the latter with a prevalence of 56.3% and a mean infection intensity of 2.6 +/-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 13 publications
(12 reference statements)
1
19
1
Order By: Relevance
“…Species of Physaloptera may occur with high prevalence (over 50%) in some populations of South American lizards of different genera and families (e.g. Vrcibradic et al, 2000, Fontes et al, 2003, Rocha et al, 2003, Bursey and Goldberg 2004. The low prevalence (under 15%) observed in the present study and in that of Vrcibradic et al (2007) suggest that lizards of the genus Enyalius are not the preferred hosts of Physaloptera spp.…”
Section: Prey Category N (%) V (%) F (%) Ixcontrasting
confidence: 49%
“…Species of Physaloptera may occur with high prevalence (over 50%) in some populations of South American lizards of different genera and families (e.g. Vrcibradic et al, 2000, Fontes et al, 2003, Rocha et al, 2003, Bursey and Goldberg 2004. The low prevalence (under 15%) observed in the present study and in that of Vrcibradic et al (2007) suggest that lizards of the genus Enyalius are not the preferred hosts of Physaloptera spp.…”
Section: Prey Category N (%) V (%) F (%) Ixcontrasting
confidence: 49%
“…Van Sluys et al, 1994;Ribas et al, 1998;Vrcibradic et al, 2000Vrcibradic et al, , 2002Fontes et al, 2003;Rocha et al, 2003;Dias et al, 2005), with studies on forest species being still scarce Bursey et al, 2005a, b). Some studies on lizard parasites have shown that the rates of parasitism and/or some parameters of the parasite communities may vary between host species/populations living in forested (i.e.…”
mentioning
confidence: 99%
“…Inglis (1968) revised Parathelandros Diesing, 1861, retaining the genus for para sites of Australian amphibians and erecting Skrjabinodon as a new genus for parasites of reptiles (Bursey & Goldberg, 1999). There are several reptile family members infected by different Skrjabinodon species were recorded by various researchers: Gekkonidae (Moravec & Baruš, 1990;Bursey & Goldberg, 1999;Hering-Hagenbeck et al, 2002;Matsuo & Oku, 2002;Jones, 2013;Bursey & Brooks, 2010), Agamidae (Rezazadeh et al, 2012), Corytophanidae (Bursey & Brooks, 2010), Iguanidae (Bundy et al, 1987;Bursey & Brooks, 2010;Bursey & Goldberg, 2007), Phrynosomatidae (Bursey & Brooks, 2010), Polychrotidae (Bursey & Brooks, 2010), Gymnophthalmidae (Bursey & Goldberg, 2011b), Lacertidae (Roca & Ferragut, 1989;Hornero & Roca, 1992;Vicente et al, 2000;Yıldırım-han et al, 2011), Anguidae , Teiidae (Bursey & Brooks, 2010), and Scincidae (Vicente et al, 2000;Hering-Hagenbeck et al, 2002;Vicente et al, 2002;Rocha et al, 2003;Bursey et al, 2008;Incedogan et al, 2014). In this study, we observed for the fi rst time Skrjabinodon sp.…”
Section: Methodsmentioning
confidence: 99%